The Case of a “Regretful” Captain: Adolfo Scilingo and the Death Flights - de Lira Rocha, Marina Maria (Revista de Historia Social y de las Mentalidades, 2024)
This article intends to analyze the causes and consequences in cases of testimony about State Terrorism in the Latin American environment when it is carried out by those responsible for violations of Human Rights. Addressing the example of public statements made by Captain Adolfo Scilingo, who worked at the Escuela de Mecánica de la Armada, during a dictatorial era, we will seek to describe the argumentative construction of these statements about his criminal actions, based on the analyzes about moral guilt and criminal guilt, carried out by Hannah Arendt, and examine the impacts that these types of speeches made by criminals had on Argentine society during the years following the declarations.
Keywords: Human Rights; Crimes against Humanity; Flights of Death; Argentina